PENGARUH PEMAHAMAN DAN PEMANFAATAN SISTEM INFOMASI AKUNTANSI TERHADAP PENINGKATAN PRODUKTIVITAS PADA PERUSAHAAN PT. PRODUK SAWITINDO JAMBI (Al Dzahab, 2023)
Purpose: This study aims to determine and analyze the effect of understanding accounting and the use of accounting information systems on increasing productivity at PT. Sawitindo Jambi products.Design/Methodology/Approach: The research method used is descriptive quantitative analysis with primary data through surveys, multiple linear regression analysis tools. Findings: The results showed that simultaneously showed that the variables of accounting understanding and accounting system utilization together had a positive and significant effect on increasing productivity at PT. Sawitindo Jambi products. while partially showing that the variable of accounting understanding has a positive and significant effect on increasing the productivity of PT. Sawitindo Jambi products. and the variable of accounting system utilization has a positive and significant effect on increasing productivity at PT. Sawitindo Jambi products.Research Implications: The implication of the research results is that the company should conduct a review of the understanding of accounting and the use of AIS in making financial reports so that the productivity of the company's financial statements can continue to be improved.